Cellulose Nanocrystals and Rice Husk Surface Functionalization Induced by Infrared Thermal Activation - Rosarita D'Orsi; Chiara Danielli; Mariachiara Spennato; Elisa Guazzelli; Elisa Martinelli; Fioretta Asaro; Lucia Gardossi; Alessandra Operamolla (ChemSusChem, 2025)
Infrared thermal activation (IRTA) is considered an efficient approach to accelerate reaction rates. The manuscript reports the first example of application of IRTA to achieve surface functionalization of cellulose nanocrystals (CNCs) under solvent-less conditions with epoxidized linoleic acid (ELA), synthesized by enzymatic approach using CaLB (lipase B from Candida antarctica) and H2O2. The final goal is to enhance the hydrophobicity of cellulosic surfaces of bio-based materials, with potential application in the coating industry. With the approach proposed in this paper, we achieve a degree of substitution of 0.09 of CNCs. The reaction is extended to delignified rice husk (d-RH), a largely available agro-waste and a cost-effective cellulose-rich biomass. Solid-state cross polarization magic angle spinning (CP MAS) 13C nuclear magnetic resonance (NMR) analyses, liquid state 1H-NMR, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), field emission scanning electron microscopy (FE-SEM) and X-ray diffractometry (XRD) data support a fine structural characterization of both functionalized CNCs and d-RH to assess the effectiveness of the strategy used and the characteristics of the materials. Water contact angle measurements confirm the changed surface chemistry and the occurrence of hydrophobization on CNCs and d-RH, revealing surfaces with modified properties and stable water contact angle of ∼40° and ∼60°, respectively. This efficient and sustainable method can have potential application in industrial-scale environments to change the properties of ligno-cellulosic biomass and bio-based materials in general.